Robot-Led Piano Lessons May Improve Cognitive Function: AFeasibility Study in a Sample with Mild Cognitive Impairment. (September 2021) - Collette, Bailey; Mois, George; Beer, Jenay M.; Boccanfuso, Laura; Ramachadran, Aditi; Gibson, Paul; Emerson, Kerstin G.; Renzi-Hammond, Lisa M.
Cognitive training has been shown to increase neural plasticity and cognitive reserve, potentially reducing the risk of developing dementia. Music learning, specifically piano playing, has been shown to be an effective form of multimodal cognitive training. This pilot study explored the feasibility and efficacy of using a socially assistive robot to provide a piano learning cognitive training intervention to older adults with mild cognitive impairment. Participants (N=11) engaged in a four-week feasibility study, which included a one-hour piano lesson per week led by a remotely controlled robot. Participants experienced improved cognitive function in the verbal memory ( p =0.04), executive function ( p= 0.01), reaction time ( p= 0.04), and cognitive flexibility ( p= 0.003) domains, as well as in the calculated neurocognitive index score ( p= 0.03). Socially assistive robots may have the potential to provide cognitive training in the form of piano lessons for older adults with mild cognitive impairment, especially adults who cannot access traditional services.